Design and performance analysis of tangential-axial flow threshing device for oat harvester - Wang, Rongxian; Zhao, Xiangpeng; Ji, Jiangtao; Jin, Xin; Li, Bin (International Journal of Agricultural and Biological Engineering, 2021)
Aiming at the problems of stalks winding and poor threshing performance in the process of mechanical harvesting of oats, a type of threshing and crushing experimental device was designed. The device was composed of a belt conveyor, a tangential-flow threshing drum, an axial-flow threshing drum, a high-speed camera and a testing device. According to a regression orthogonal test method, using the rotation speed of the axial-flow drum, the horizontal center distance, and the vertical height difference of the two threshing drums as experimental factors; using the mass fraction of long stalks and the threshing rate as experimental indexes, a mathematical regression model of factors and indexes was established, and combined parameters were analyzed for the threshing quality and crushing ability. Experimental results showed that this device had the best crushing performance when the rotation speed of the axial-flow drum was 850 r/min, the horizontal center distance was 820 mm, and the vertical height difference was 10 mm, and this device had optimal threshing performance when the rotation speed of the axial-flow drum was 760 r/min, the horizontal center distance was 820 mm, and the vertical height difference was 20 mm. The parameters were optimized by Design-Expert 11 to obtain an optimization result that the rotation speed of the axial-flow drum was 800 r/min, the horizontal center distance was 820 mm, and the vertical height difference was 10 mm. A verification experiment was carried out by using a high-speed camera, and the two groups of parameters were selected for a comparative experiment. Images of material movement between the two threshing drums were captured by the high-speed camera. Experimental results showed that the optimized parameters were beneficial to improving the threshing performance and anti-winding performance of the oat threshing process. This study provides a technical basis for the research and development of oat combine harvesters. Keywords: tangential-axial flow threshing device, oat, parameter optimization, threshing performance, crushing performance DOI: 10.25165/j.ijabe.20211406.6173 Citation: Wang R X, Zhao X P, Ji J T, Jin X, Li B. Design and performance analysis of tangential-axial flow threshing device for oat harvester. Int J Agric & Biol Eng, 2021; 14(6): 61–67.